Cystatin C predicts cognitive decline in multiple system atrophy: A 1-year prospective cohort study - Zhang, Lingyu; Li, Ruicen; Hou, Yanbing; Cao, Bei; Wei, Qianqian; Ou, Ruwei; Liu, Kuncheng; Lin, Junyu; Yang, Tianmi; Xiao, Yi; Huang, Wenxia; Shang, Huifang (Frontiers in Aging Neuroscience, 2022)
Background: Accumulating evidence has suggested that cystatin C is associated with cognitive impairment in patients with neurodegenerative diseases. However, the association between cystatin C and cognitive decline in patients with multiple system atrophy (MSA) remains largely unknown. Objectives: The objective was to determine whether cystatin C was independently associated with cognitive decline in patients with early-stage MSA. Methods: Patients with MSA underwent evaluation at baseline and the 1-year follow-up. Cognitive function was evaluated with Montreal cognitive assessment (MoCA). Changes in the MoCA score and the absolute MoCA score at the 1-year assessment were considered the main cognitive outcome. The cystatin C concentrations in patients with MSA and age, sex, and body mass index matched-healthy controls (HCs) were measured. A multiple linear regression model was used to test the association between cystatin C and cognitive decline. Results: A total of 117 patients with MSA and 416 HCs were enrolled in the study. The cystatin C levels were significantly higher in patients with MSA than in HCs (P<0.001). Cystatin C levels were negatively correlated with MoCA score at baseline and at 1-year follow-up. Multiple linear regression model adjusted for potential confounders showed that baseline cystatin C levels were significantly associated with the MoCA score (P=0.004) or change in the MoCA score (P=0.008) at 1-year follow-up. Conclusions: Our results suggested that cystatin C may serve as a potential biomarker of cognitive decline in patients with early-stage MSA.